2007
DOI: 10.2196/jmir.9.2.e17
|View full text |Cite
|
Sign up to set email alerts
|

A Field Test of a Web-Based Workplace Health Promotion Program to Improve Dietary Practices, Reduce Stress, and Increase Physical Activity: Randomized Controlled Trial

Abstract: Background Most work sites engage in some form of health promotion programming designed to improve worker health and reduce health care costs. Although these programs have typically been delivered through combinations of seminars and print materials, workplace health promotion programs are increasingly being delivered through the Internet.Objective The purpose of this research was to evaluate the effectiveness of a Web-based multimedia health promotion program for the workplace, designed to improve dietary pra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
247
1
11

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(272 citation statements)
references
References 26 publications
5
247
1
11
Order By: Relevance
“…All e-learning interventions were delivered in high-income countries, and the majority of interventions were delivered in the USA [42][43][44][45][47][48][49][50][51][52][53]55,56,58,59,62,64,66,[70][71][72][73][74][75][80][81][82][83][84] research groups dedicated to e-learning and diet research; hence, the geographic clustering of studies. For example, a single large e-learning research group produced all eight RCTs set in the Netherlands and Belgium.…”
Section: 83mentioning
confidence: 99%
See 2 more Smart Citations
“…All e-learning interventions were delivered in high-income countries, and the majority of interventions were delivered in the USA [42][43][44][45][47][48][49][50][51][52][53]55,56,58,59,62,64,66,[70][71][72][73][74][75][80][81][82][83][84] research groups dedicated to e-learning and diet research; hence, the geographic clustering of studies. For example, a single large e-learning research group produced all eight RCTs set in the Netherlands and Belgium.…”
Section: 83mentioning
confidence: 99%
“…Twenty-four studies reported on actual use of intervention programs, either making use of automated logon or usage features within programs (16 studies 42,48,53,59,[62][63][64]66,69,71,74,77,79,80,82,84 ) or obtaining self-reported usage data from participants (three studies 52,58,60 ). Five studies 44,55,57,70,80 reported collecting usage data, but did not state how.…”
Section: Mode Of Deliverymentioning
confidence: 99%
See 1 more Smart Citation
“…A recent randomized trial found Ebert et al moderate effect sizes with regard to the reduction of depressive symptoms among stressed teachers (6,14), whereas another trial did not find beneficial effects of a problem-solving training on depression or work-related outcomes (15,16). So far, randomized controlled trials (RCT) on internet-based SMI show mixed results with some studies reporting significant results with moderate effects sizes on perceived stress (17)(18)(19) and others yielding non-significant outcomes (20,21). Our group recently conducted a RCT testing the efficacy of an internet-based stress management intervention (iSMI) among employees with heightened levels of perceived stress (22,23).…”
mentioning
confidence: 99%
“…(G2) Em estudo de revisão integrativa da literatura sobre os distúrbios osteomusculares relacionados ao trabalho em profissionais de enfermagem, Lelis et al (2012), recomendam investimentos em programas preventivos e educação em saúde. A utilização de recursos da internet tem apresentado resultados satisfatórios em programas de promoção da saúde com os temas de bem estar, gestão do estresse, alimentação saudável e controle de peso, bem como, fomentar a prática de atividade física com recursos que poderiam ser disponibilizados pela própria instituição (Cook et al, 2007).…”
Section: A Capacidade Para O Trabalho O Presenteismo E Demais Fatoreunclassified